HUBUNGAN STATUS GIZI, POLA ASUH DAN PENGETAHUAN IBU TENTANG POLA ASUH DENGAN TINGKAT KEMANDIRIAN ANAK USIA PRA SEKOLAH DI TK NEGERI 02 KECAMATAN SUNGAI PAGU KAB. SOLOK SELATAN TAHUN 2017 - Rachma Yuliandini; Nurhamidah Nurhamidah (JURNAL KESEHATAN PERINTIS, 2018)
Nutritional status, care pattern and mother’s knowledge about care pattern is the best substance for establishment children’s personality. The important of care pattern is feeding the child, taking care the child, and child’s cleannesses. The differences of nutritional status, care pattern and mothert’s knowledge about care pattern causes different child’s autonomy levels. The purpose of this research is to knew relationship of nutritional status, care pattern, mother’s knowledge about care pattern with autonomy levels to children preschool age at TK Negeri 02 Sungai Pagu Kabupaten Solok Selatan year 2017. This research is descriptive with the desain cross-sectional study. The population and sample in this research is all of children who followed education in kindergarten (TK) Negeri 02 Sungai Pagu Kabupaten Solok Selatan, and student’s parents Taking the sample did by used population sampling method toward 60 peoples. Collecting the data did by interview, measuring of anthropometry weight and height of body, instrument of the research to care pattern variable, knowledge about care pattern and autonomy is questionnaire, and to nutritional status variable anthropometry measurement. The data was processed by uses univariat and bivariat analysis with testing Chi Square. From the research result obtained as much (28, 3 %) the children was not autonomy, (28, 3 %) children was undernourished, (38,3 %) children had less care pattern, and (36,7 %) had less knowledge about care pattern. From the result of statistic test, each variable was that p-value 0,000<0,05 it means that there was meaningful relationship between of nutritional status with autonomy, and knowledge about care pattern with autonomy. The conclusion from the researchis there was meaningful relationship between of nutritional status, care pattern, and mother’s knowledge about care pattern with autonomy levels to children preschool age at TK Negeri 02 Sungai Pagu Kabupaten Solok Selatan year 2017.